Use of fly ash and ash stabilizer in construction - Isaac, Dorivaldo Capusso Luiele (Univerzita Pardubice, 2014)
The main purpose of this thesis is to analyze the use of fly ash and ash stabilizer in construction, this fly ash was acquired in an industrial miner screw ECHVA. At the beginning is detailed the characteristics and composition of the fly ash, their classification and application. In the end is presented tests of permeability, shear test, uniaxial compressive test and respective results.
Využití popílků a popílkového stabilizátu v dopravním stavitelství
Keywords: fly ash; ash stabilizer; composition of fly ash